Label-free multiphoton microscopy reveals altered tissue architecture in hippocampal sclerosis - Uckermann, Ortrud; Galli, Roberta; Leupold, Susann; Coras, Roland; Meinhardt, Matthias; Hallmeyer-Elgner, Susanne; Mayer, Thomas; Storch, Alexander; Schackert, Gabriele; Koch, Edmund; Blümcke, Ingmar; Steiner, Gerald; et al. (Epilepsia, 2017)
The properties and structure of tissue can be visualized without labeling or preparation by multiphoton microscopy combining coherent anti-Stokes Raman scattering (CARS), addressing lipid content, second harmonic generation (SHG) showing collagen, and two-photon excited fluorescence (TPEF) of endogenous fluorophores. We compared samples of sclerotic and nonsclerotic human hippocampus to detect pathologic changes in the brain of patients with pharmacoresistant temporomesial epilepsy (n = 15). Multiphoton microscopy of cryosections and bulk tissue revealed hippocampal layering and micromorphologic details in accordance with reference histology: CARS displayed white and gray matter layering and allowed the assessment of axonal myelin. SHG visualized blood vessels based on adventitial collagen. In addition, corpora amylacea (CoA) were found to be SHG-active. Pyramidal cell bodies were characterized by intense cytoplasmic endogenous TPEF. Furthermore, diffuse TPEF around blood vessels was observed that co-localized with positive albumin immunohistochemistry and might indicate degeneration-associated vascular leakage. We present a label-free and fast optical approach that analyzes pathologic aspects of HS. Hippocampal layering, loss of pyramidal cells, and presence of CoA indicative of sclerosis are visualized. Label-free multiphoton microscopy has the potential to extend the histopathologic armamentarium for ex vivo assessment of changes of the hippocampal formation on fresh tissue and prospectively in vivo.
EVALuna2:7366